2022
DOI: 10.3389/fimmu.2022.984666
|View full text |Cite
|
Sign up to set email alerts
|

Tumor microenvironment features decipher the outperformance of neoadjuvant immunochemotherapy over chemotherapy in resectable non-small cell lung cancer

Abstract: This study evaluated the efficacy of neoadjuvant immunochemotherapy (Io+Chemo) versus chemotherapy alone (Chemo) in resectable non–small cell lung cancer (NSCLC) in a real-world setting. The association of tumor immune microenvironment (TIME) with pathologic response to different neoadjuvant therapies was also explored.Stage I−III NSCLC patients who received Io+Chemo or Chemo alone followed by surgery were included in the study. Tumor tissues collected during surgery were subjected to TIME evaluation using mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…In addition, neoadjuvant PD-1/L1 inhibitors could utilize high tumor antigen levels in the primary tumor to enhance T-cell priming [23]. Other studies have shown that neoadjuvant immunochemotherapy can upregulate the expression of PD-L1 and TILs [24]. Both neoadjuvant immunochemotherapy and neoadjuvant radiotherapy can upregulate PD-L1 expression [25], which supports our current research ndings.…”
Section: Discussionsupporting
confidence: 88%
“…In addition, neoadjuvant PD-1/L1 inhibitors could utilize high tumor antigen levels in the primary tumor to enhance T-cell priming [23]. Other studies have shown that neoadjuvant immunochemotherapy can upregulate the expression of PD-L1 and TILs [24]. Both neoadjuvant immunochemotherapy and neoadjuvant radiotherapy can upregulate PD-L1 expression [25], which supports our current research ndings.…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, for 26 patients in whom lymph node metastasis was highly suspected, there was no tumor cell residue in lymph nodes as confirmed pathologically after neoadjuvant therapy. Previous research ( 7 ) indicates that neoadjuvant immunochemotherapy can eradicate tumor cells by impacting the tumor microenvironment. The concomitant use of immunotherapy with chemotherapy could stimulate the immune system, enhancing the efficacy of the body’s T and B cells in eliminating tumor cells for an extended period.…”
Section: Discussionmentioning
confidence: 99%
“… 17 The presence of TLS has also provided new insights into the mechanism by which neoadjuvant chemoimmunotherapy is preferable to chemotherapy from the perspective of the tumor microenvironment. 18 However, few studies have explored the exact relationship between TLS and clinical prognosis in terms of its expression and maturation.…”
Section: Introductionmentioning
confidence: 99%